METODA CRAMER UNTUK SOLUSI ANALISA RANGKAIAN LISTRIK MENGGUNAKAN SCILAB - Khoirul Anam; Yenni Arnas (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Many problems in electrical circuit analysis are widely used mathematical models in their completion. The mathematical model is then formulated numerically in the Linear Equation System. The linear equation can be solved using several Numerical Methods, namely the Gauss Elimination Method, the Cramer method, the Inverse Matrix Method, the Gauss-Jordan Elimination Method and others. To calculate m equations with an unknown number of n variables from large and complex systems, it takes a long time and is not efficient. to complete large and complex mathematical calculations with an easy way to use the Scilab program. At this writing the authors limit only the completion of the Linear Equation System using Scilab with the Cramer Method.